Prenatal care in rural communities: Challenges and strategies for nurses in the Family Health Strategy (Research, Society and Development, 2025)
Introduction: Prenatal care is the regular follow-up carried out by pregnant women to monitor their health and that of the baby during pregnancy, aiming to prevent or diagnose early disorders and diseases such as anemia and gestational hypertension. Objective: To analyze the challenges faced and the strategies used by nurses in the Family Health Strategy (FHS) to promote prenatal care in rural communities. Methodology: This is an integrative literature review. Data collection took place between August and November 2024. The databases used were SciELO, MEDLINE, and Google Scholar, including full-text articles in Portuguese and English published between 2010 and 2025. In total, six articles met the inclusion criteria. Results: The findings indicate that, despite advances in prenatal care in rural areas, challenges such as resource shortages, geographic barriers, and limited access to health services persist. Conversely, the role of nurses in the FHS is highlighted, especially through educational strategies, strengthening bonds with pregnant women, and health promotion actions, which contribute to greater adherence to prenatal follow-up. Conclusion: Prenatal care in rural communities is essential to reduce maternal and neonatal risks and to strengthen the bond between health professionals and pregnant women. However, barriers such as distance, lack of resources, and structural limitations still hinder proper adherence. Thus, the role of nurses in the FHS is fundamental to expand follow-up throughout pregnancy and the puerperium, reducing complications and promoting more humane and accessible care.